Efficacy and safety of eribulin in taxane-refractory patients in the 'real world'. (May 2017) - Lorusso, Vito; Cinieri, Saverio; Latorre, Agnese; Porcu, Luca; Del Mastro, Lucia; Puglisi, Fabio; Barni, Sandro
Aim: Recent clinical, randomized and observational studies showed that eribulin, an analogous of Halichondrin B, was beneficial and well-tolerated in heavily pretreated metastatic breast cancer patients. Here, we aim to evaluate the effectiveness and safety of eribulin in taxane-refractory metastatic breast cancer patients.Patients & methods: In this subanalysis of the ESEMPIO study database, we selected 91 subjects with well-defined taxane refractoriness and complete data available.Results: 41 patients (45.2%) showed clinical benefit; one complete response (2.2%) and 16 partial responses (17.6%) were observed. Median progression-free survival and median overall survival were 3.1 and 11.6 months, respectively. The most experienced adverse event was asthenia/fatigue (58%), followed by neutropenia (30%). The treatment-related toxicity led to eribulin-dose reduction in 19 patients and suspension in nine.Conclusion: This study shows that eribulin is effective and well tolerated also in taxane-refractory patients in clinical practice.